Effect of Supply Chain Management Practices on Financial and Economic Sustainable Performance of Indonesian SMEs - Christina Whidya Utami; Hendro Susanto; Fanny Septina; Yoseva Maria Pujirahayu Sumaji; Ikbar Pratama (International Journal of Supply Chain Management, 2019)
In contemporary business environment firms focus on sustainable Financial and Economic performance. Sustainable performance of the firms happens is the result of continuous value generation for shareholders and stakeholders of firm. This study intended to investigate the effect of Supply Chain Management Practices (SCMP) on Financial and Economic Sustainable Performance of Indonesian SMEs. For the achievement of the objective of study, researcher used quantitative research approach and questioner method was applied for the collection of data. To fulfil the objectives of this study, the data was collected from the managing directors, supply chain managers, planning managers, and procurement managers. PLS-SEM approach was carried out by the study for the examination hypotheses. The results of study concluded that SCM Practices have significant and positive influence on Financial and Economic Sustainable Performance of Indonesian SMEs. Moreover, findings of this study indicated that effective application of SCMP could enhance the financial and economic performance of the SMEs in developing countries. Findings of the study highlighted that the relationship with customer, strategic supplier integration and level of information sharing is necessary for financial and economic sustainable performance of SMEs. This study contributes to Supply chain literature and offer new empirical evidence that supply chain management practices are significant for sustainable financial performance. However, this study used only three SCM practices (relationship with customer, strategic supplier integration and level of information sharing), the other important aspects of SCM practices such as SCM formulation, implementation and evaluation would be used in future research.